1999
DOI: 10.1038/18796
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine induces migration of waterfleas

Abstract: diameter) per treatment. The tubes were then placed in a water bath with a temperature gradient from top to bottom of 20 to 10 °C. We used a spectrophometric assay procedure 10 to establish the TMA concentration in 10 litres of the medium that had previously contained four fish (ides, Leuciscus idus, 10 cm long), and recorded the resulting vertical migration behaviour of daphnids exposed to this medium. TMA concentration in this 'fish' water was between 10 and 25 ȖM.We found that even low concentrations of TMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 2 publications
4
35
0
1
Order By: Relevance
“…A reliable operation is required at least for 1 week, the test setup needs to be easy to handle with less than 3 h of maintenance per week, and it should automatically detect alarm situations [6]. Daphnia (water fleas) respond to toxins by changing their activity which is manifested in a change in motility [7,8]. Such dynamical Daphnia tests were successfully applied at the Rhine river and seem to be especially useful to detect low concentrations of insecticides [9].…”
Section: Biological Systems Respond Sensitively To External Cuesmentioning
confidence: 99%
“…A reliable operation is required at least for 1 week, the test setup needs to be easy to handle with less than 3 h of maintenance per week, and it should automatically detect alarm situations [6]. Daphnia (water fleas) respond to toxins by changing their activity which is manifested in a change in motility [7,8]. Such dynamical Daphnia tests were successfully applied at the Rhine river and seem to be especially useful to detect low concentrations of insecticides [9].…”
Section: Biological Systems Respond Sensitively To External Cuesmentioning
confidence: 99%
“…Inducible defenses allow organisms to reap the benefits of a defense, while saving potential costs associated with investment in the defense. The cue transferring information of a predation risk is generally thought to be a chemical substance released by the predator, al- 1 E-mail: Lars-Anders.Hansson@limnol.lu.se though few such chemicals have actually been identified (Boriss et al 1999, Brö nmark and Hansson 2000, von Elert and Pohnert 2000. These cues, and others like them, can be considered a ''chemical information network'' (Hansson 2000a), and their possible existence may have a profound impact on our understanding of ecological systems.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper by Boriss et al (1999) reported that trimethylamine (TMA) induces diel vertical migration in Daphnia and it is a biologically active component of the fish-exuded kairomone. If indeed TMA were an ecologically relevant cue, it should also induce characteristic antipredator life history shifts.…”
mentioning
confidence: 99%
“…The concentrations used in this study were based on the results of Boriss et al (1999), so that the lower level was chosen to represent TMA concentration in naturally produced fish exudate and the higher to match that which was reported to induce pronounced migration behavior. The lower concentrations used (10-20 M) produced rather weak effects, but these effects were in the same direction as the effects of higher TMA concentrations.…”
mentioning
confidence: 99%